Performativity of JaF art agency on the land, city, and its surroundings - Sudarmanto, Joni Agung (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
This study aims to see the performativity of terracotta through the process and the culture of the roof tile production industry in Jatiwangi District, Majalengka Regency, West Java. This research used qualitative methods, and collecting data used a combination of three methods: literature study, participatory observation, and semi-structured interviews. After the data is collected, the next step is data analysis using the concept of performativity and art agency. JaF emerged by taking on the role of a change agent, inviting Jatiwangi residents, especially roof tile industry players, to survive together and stay true to their native culture using participatory arts engagement. Perform various artistic activities with Jatiwangi residents to declare that they exist. They are using artistic approaches to narrate defensive actions, holding various forms of art festivals to show their progress in Jatiwangi. This is due to the performativity of roof tiles as the initial trigger, the community, and the development of Jatiwangi as an "art factory" into Jatiwangi Art Factory (JaF). So, in JaF, roof tiles, artisans, artists, cultural actors, terracotta, and the "art factory" brand is a performance agency in the land, city, and surroundings Performativitas badan seni di daerah, kota, dan sekitarnya di JaF Penelitian ini bertujuan untuk melihat performativitas terakota melalui proses dan budaya industri produksi genteng di Kecamatan Jatiwangi, Kabupaten Majalengka, Jawa Barat. Penelitian ini menggunakan metode kualitatif, dan pengumpulan data menggunakan kombinasi tiga metode: studi kepustakaan, observasi partisipatif, dan wawancara semi terstruktur. Setelah data terkumpul, langkah selanjutnya adalah analisis data dengan menggunakan konsep performativity dan art agency. JaF muncul dengan mengambil peran sebagai agen perubahan, mengajak warga Jatiwangi, khususnya pelaku industri genteng, untuk bertahan bersama dan tetap setia pada budaya asli mereka melalui keterlibatan seni partisipatif. Melakukan berbagai kegiatan seni bersama warga Jatiwangi untuk menyatakan bahwa mereka ada. Mereka menggunakan pendekatan artistik untuk menceritakan tindakan defensif, mengadakan berbagai bentuk festival seni untuk menunjukkan kemajuan mereka di Jatiwangi. Hal ini dikarenakan performativitas genteng sebagai pemicu awal, masyarakat, dan berkembangnya Jatiwangi sebagai “pabrik seni” menjadi Jatiwangi Art Factory (JaF). Jadi, di JaF, genteng, pengrajin, seniman, aktor budaya, terakota, dan merek "pabrik seni" adalah agensi pertunjukan di tanah, kota, dan sekitarnya.